Carbon‐Based Composite as an Efficient and Stable Metal‐Free Electrocatalyst. (8th April 2016) - Fan, Xiujun; Peng, Zhiwei; Wang, Juanjuan; Ye, Ruquan; Zhou, Haiqing; Guo, Xia
Abstract : Silicon carbide (SiC) encapsulated with graphitized nanodiamond (GD) sheaths (SiC‐GD) as a core–shell nanocrystal (NC) is synthesized with atomic H post‐treatment of vertically aligned carbon nanotubes, which are unzipped and converted into graphene nanoribbons (GNRs) and preserve their vertically aligned integrity. The SiC‐GD core–shell NCs anchor on the GNRs framework and form SiC‐GD@GNRs composite. The nucleation and growth mechanisms for single crystal nanodiamond without diamond seed are discussed. The SiC‐GD@GNRs composite as a metal‐free electrocatalyst exhibits a high activity in the hydrogen evolution reaction, with a small onset overpotential of 8 mV, Tafel slope of 54 mV dec −1, and exchange current density @ 200 mV of 77.4 mV, as well as long term stability in acid medium. The superior electrocatalytic performances of SiC‐GD@GNRs are ascribed to a high dispersion of SiC‐GD NCs on the GNRs support and a high stability of the GD and GNRs in acid solution. Abstract : Silicon carbide (SiC) encapsulated with graphitized nanodiamond (GD) sheaths (SiC‐GD) as a core‐shell nanocrystal is synthesized with atomic hydrogen post‐treatment of vertically aligned carbon nanotubes, which are unzipped and converted into graphene nanoribbons (GNRs). The SiC‐GD@GNRs composite is self‐assembled with SiC, GD clusters, and GNRs into an integrated nanostructure, leading to excellent hydrogen evolution reaction activity.